Climate and economic development in the tropics - Lee, Douglas H. K. (New York: Published for the Council on Foreign Relations by Harper & Brothers, 1957)
With the keen interest displayed of recent years in the problems of the underdeveloped countries, the author finds reason to assess once more the effect of hot climate on economic developments. Much of the writing has been by what the of this book calls the "cornucopia boys" who claim the tropical climate countries are the lands of the future, or by the pessimists, who rule out such countries as having no future whatsoever.
Bibliography: p. 177-182.
ne 3/04/2018
Loans
Keywords: Agriculture; Tropics; Developing countries